KURIKULUM MATA KULIAH PENGEMBANGAN KEPRIBADIAN PENDIDIKAN AGAMA ISLAM UNIVERSITAS ISLAM â€œ45â€ BEKASI - Khoir HS, Abdul (Turats, 2011)
This article will discuss about the course curriculum Personality Development Islamic Education at Islamic University "45" Bekasi. From this article it can be concluded that the Islamic Religion Education is taught to students aims to increase faith, understanding, appreciation and practice of Islam about to become a pious Muslim man, a certain character and personality have a competent manner, democratic and accountable. While the specific objectives defined in the outline points of Islamic Religion Education learning materials.